2019
DOI: 10.1155/2019/9405939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rainfall and Temperature Conditions for a Perennial Crop in Tropical Wetland: A Case Study of Cocoa in Côte d’Ivoire

Abstract: e rainfall and temperature conditions are evaluated for the first time during the 1989-2006 period, in six main cocoa production areas (Abengourou, Agboville, Daloa, Dimbokro, Guiglo, and Soubre) of Côte d'Ivoire using data from SODEXAM (groundbased observation) and the ex-CAISTAB. Statistical analysis shows an important sensitivity of cocoa production to rainfall conditions in all regions. It is worth noting that only the major rainy season from April to July and the rainfall amount of the little dry season f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 19 publications
1
31
0
4
Order By: Relevance
“…Côte d'Ivoire consists of three climatic zones with di erent seasonal precipitation cycles [34,40,41]: (i) the Northern zone (mainly grassy savanna) presents a unique rainy season that occurs during the boreal summer (July-August-September) with a peak of about 270 mm in August, (ii) the Central zone (forested savanna and deteriorated forest) presents two rainy seasons with two maxima in June and September, and (iii) the coastal zone (forest and swamp) also presents two rainy seasons with a major peak in June (up to 500 mm) and a second maximum, less pronounced in October (120 mm). e population in Côte d'Ivoire is estimated at more than 22 million [42], of which about 70% live off the income from agricultural activities that were affected by the climate change, particularly extremes in temperature and rainfall conditions [43]. In addition, previous studies [44][45][46] showed that during the five last decades (i.e., 1962-2012), Côte d'Ivoire faced a significant warming estimated at about 0.5°C (mean value) compared to the 1961-1990 normal period (i.e.…”
Section: Study Areamentioning
confidence: 99%
“…Côte d'Ivoire consists of three climatic zones with di erent seasonal precipitation cycles [34,40,41]: (i) the Northern zone (mainly grassy savanna) presents a unique rainy season that occurs during the boreal summer (July-August-September) with a peak of about 270 mm in August, (ii) the Central zone (forested savanna and deteriorated forest) presents two rainy seasons with two maxima in June and September, and (iii) the coastal zone (forest and swamp) also presents two rainy seasons with a major peak in June (up to 500 mm) and a second maximum, less pronounced in October (120 mm). e population in Côte d'Ivoire is estimated at more than 22 million [42], of which about 70% live off the income from agricultural activities that were affected by the climate change, particularly extremes in temperature and rainfall conditions [43]. In addition, previous studies [44][45][46] showed that during the five last decades (i.e., 1962-2012), Côte d'Ivoire faced a significant warming estimated at about 0.5°C (mean value) compared to the 1961-1990 normal period (i.e.…”
Section: Study Areamentioning
confidence: 99%
“…Penelitian Yoroba et al (2019) menunjukkan bahwa dampak curah hujan dan kondisi suhu terhadap hasil kakao terlihat di beberapa tempat yang diamati. Peningkatan jumlah curah hujan selama musim hujan utama cenderung mengurangi hasil kakao.…”
Section: Pendahuluanunclassified
“…Peningkatan jumlah curah hujan selama musim hujan utama cenderung mengurangi hasil kakao. Suhu dan curah hujan selama musim hujan utama dan musim kemarau kecil sangat penting untuk menjelaskan variasi produksi kakao (Yoroba et al, 2019). Dengan demikian, faktor iklim menarik untuk dikaji lebih dalam karena erat kaitannya dengan penurunan produktivitas kakao.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Extreme rainfall fluctuations allow the plant to experience a water deficit (Mishraa and Cherkauer 2010;Bari et al 2016;Medina and Laliberte 2017) which impacts on its final production (Zlatev and Lidon 2012). Cocoa is a very sensitive plant to drought stress (Carr and Lockwood 2011;Amos and Thompson 2015;Gateau-Rey et al 2018;Santhyami et al 2018;Yoroba et al 2019). Drought stress causes seedling mortality, fruit and seed size reduction, and the increase of pest and disease attacks on cocoa (Atayese et al 2013;Longe and Oyekale 2013;Santos et al 2014;Ofori et al 2015;Gateau-Rey et al 2018).…”
Section: Introductionmentioning
confidence: 99%